A controlled trial of glycopyrronium and l-hyoscyamine in the long-term treatment of duodenal ulcer. Issue 7 (July 1970) - Kaye, Michael D.; Rhodes, J.; Beck, Peter; Sweetnam, Peter M.; Davies, G. T.; Evans, K. T.
Abstract : A controlled single-blind trial has been carried out to determine the value of long-term anticholinergic therapy in duodenal ulcer. Of 106 male patients with symptomatic and radiologically proven duodenal ulcer admitted to the trial, 91 completed the study. Patients were divided randomly into three groups. They received either glycopyrronium, or 1-hyoscyamine in a sustained-release form, or inert tablets for one year. Progress was judged on the basis of frequency and severity of symptoms, monthly assessments by patients, antacid consumption, and radiology. By all criteria, glycopyrronium and 1-hyoscyamine were not significantly superior to placebo. Symptomatic improvement, both subjective and objective, occurred in approximately 80% of all patients during the year of observation; there was no significant difference between the groups.